Social Support and Personal Resilience of Government Employees (International Journal of Scientific Research and Management (IJSRM), 2021)
The study primarily aims to determine which domain of social support significantly influences the personal resilience of government employees. The study utilized a descriptive correlational design and employed a survey method to attain the research objectives. The selected respondents were the 210 government employees who were selected through a stratified random sampling technique. The researchers made use of the pilot-tested and enhanced adapted questionnaires. The statistical tools used were mean, pearson r and regression. As reflected on the results, social support and personal resilience of government employees obtained different mean scores but both belong to high descriptive levels. Further, it was found out that there is a significant relationship between social support and the personal resilience of government employees. Furthermore, it was found that social support significantly influences personal resilience having three out of four domains contributed to its significant influence. Lastly, it was emotional support emerged as the best predictor in this study. Keywords: public administration, social support, personal resilience, emotional support, Philippines